Penerapan Pendekatan Inkuiri dalam Meningkatkan Hasil Belajar IPS Siswa Kelas V SD Inpres Malakaya Kabupaten Gowa - St Arminah; Hidayah Quraisy; Syarifah Aeni Rahman (Journal Innovation In Education, 2023)
The problem that occurs in class V SD Inpres Malakaya is the lack of application of a learning approach resulting in learning that tends to be boring and low social studies learning outcomes.This research is a Classroom Action Research (CAR) which aims to find out the increase in social studies learning outcomes by applying an inquiry approach in Class 5 of SD Inpres Malakaya, Gowa Regency. Learning is carried out for 2 cycles, each cycle has 4 stages, namely: planning, implementing, observing, and reflecting. Data collection tools in this study are observation, tests, and documentation.Student learning outcomes in cycle I showed that 11 students who completed social studies had completed the KKM with the highest score of 75, then the test was continued again in cycle II with a slight improvement in that students' learning outcomes in cycle II increased, as many as 20 students fulfilled the KKM. with the highest score of 100. Based on the results of the classroom action research that has been done, it can be concluded that the application of the inquiry approach can improve social studies learning outcomes for 5th grade students of SD Inpres Malakaya, Gowa Regency. With a completeness value in the first cycle of 50% and in the second cycle of 91%. So from cycle I to cycle II the social studies learning outcomes of students increased by 41%.